DEVELOPMENT OF ELECTRONIC MODULE BASED ON GREEN CHEMISTRY ON REACTION RATE MATERIAL - Bella Yunitamara; Sri Mulyanti; Wiwik Kartika Sari (Jurnal Education and Development, 2023)
One of the effects of revolution 4.0 on the educational landscape is a shift in student perspectives. The instructional materials used as a learning aid must be customized to each student's needs. One of the issues with learning chemistry is that students often don't understand the concepts of reaction rates and green chemistry. The goal of this project was to provide educational materials in the form of electronic modules based on reaction rate material in green chemistry. A 4-D model of define, design, develop, and disseminate is employed in the research process, but only up until the develop step. The methods used to acquire the data were interviews, questionnaires, and documentation. Data analysis was carried out by using expert validity tests and practicality tests by students. Based on the results of data analysis, it is known that expert validation obtained an average score of 0.82 with a valid category, while the results of student responses got an average percentage of 88.78% in each aspect that was included in the very good category and very practical to use.